The Palgrave Handbook of Chinese Language Studies - Ye, Zhengdao (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
This major new reference work provides a comprehensive overview of linguistic phenomena in Mandarin and other dialects in a global context, highlighting the dynamic interaction between those languages and English. Through state-of-the-art accounts of various sub-fields such as applied linguistics, machine translation, English subtitling as cross-cultural mediation, technology in Chinese language teaching and global business communication, this Handbook offers a significant contribution to the field of Chinese language and linguistics. Examining fast-growing linguistic research areas on Chinese languages, ranging from research on language contact, Linguistic Typology, Cognitive Linguistics, Pragmatics, Forensic Linguistics, to Sinitic Kinship studies, it focuses on language contact situations inside and outside China, including the Cantonese and Hokkien diaspora, and Sinitic languages notably along the Belt and Road. Exploring how key Chinese concepts were coined at the beginning of the 20th century through interaction with European languages and how they have evolved, it also includes topics on the search for a universal language in the Chinese language context. Addressing core issues within Chinese language and culture and focusing on the sites and forms of interaction between Chinese and English, this Handbook encompasses a rich overview of the field, offering a global and interdisciplinary tool for students and researchers across the field of Chinese language and linguistics.
1. Research on Language Contact -- 2. Typology Studies in China -- 3. Cognitive Linguistics in China -- 4. Pragmatic Studies in China -- 5. Forensic Linguistics on Chinese -- 6. Sinitic Kinship Semantics -- 7. The Study of Classical Chinese in Europe -- 8. Language situations in contemporary China -- 9. Cantonese Diaspora -- 10. Language Contact: Shanghai Wu -- 11. Sinitic Languages along the Belt and Road -- 12. Hokkien in Diaspora -- 13. 'Migrating concepts' in Chinese -- 14. Chinese-English Bilingual Dictionaries -- 15. Chinese and the Search for a Universal Language: from Enlightenment to Contemporary times -- 16. Machine Translation -- 17. Translating Chinese Law -- 18. Chinese children literature in English translation -- 19. Translating films on ethnic minorities into English -- 20. Subtitling in English as cross-cultural mediation -- 21. Subtitling in Chinese -- 22. Technology in Chinese Language Teaching -- 23. Cultural Performance Approach in Chinese language teaching -- 24. Cultural Key Words in Mandarin Chinese -- 25. Mandarin-Speaking Children in Britain -- 26. Chinese as a mother tongue in the context of Global Business English Communication -- 27. Chinese and Singaporean English -- 28. From Kowtow to Gaokao: New Chinese Terms in English language media.
Keywords: Applied linguistics; Communication; Linguistics; Genetic transcription; Intercultural communication; Applied Linguistics; Media and Communication; Linguistics; Gene Transcription; Intercultural Communication